Clinical Values of miR-23a-3p in Oral Lichen Planus and Its Role in Keratinocyte Proliferation and Inflammatory Response - Wang J; Hu M; Li L (Dove Medical Press, 2021)
Jian Wang,1,* Mingyan Hu,2,* Leilei Li2 1Department of Stomatology, Dongying Hospital of Traditional Chinese Medicine, Dongying, Shandong, 257000, People's Republic of China; 2Department of Stomatology, Dongying People's Hospital, Dongying, Shandong, 257091, People's Republic of China*These authors contributed equally to this workCorrespondence: Leilei LiDepartment of Stomatology, Dongying People's Hospital, No. 317, South Dongcheng Road, Dongying, 257091, Shandong, People's Republic of ChinaTel/Fax +86-546-8901234Email lileileidongying@163.comPurpose: Oral lichen planus (OLP) is a chronic inflammatory disease occurring in the oral cavity, and several miRNAs have been identified to be involved in the disease progression and malignant transformation. This study investigated the expression changes of miR-23a-3p in OLP patients, and further explored its functional role in keratinocyte cell proliferation and inflammatory response.Patients and Methods: Fifty buccal mucosal tissue samples were collected from OLP patients. HaCaT cells were cultured with lipopolysaccharides (LPS) to mimic the condition of OLP in vitro. RNA extraction and quantitative real-time PCR (qRT-PCR) were used for the measurement of miR-23a-3p levels. The cell viability and inflammation were detected by using cell counting kit-8 (CCK-8) and enzyme-linked immunosorbent assay (ELISA). The target gene of miR-23a-3p was verified by using luciferase reporter assay.Results: Compared with the control group, miR-23a-3p was significantly downregulated in the buccal mucosal tissues of OLP patients, and a remarkably decreased level of miR-23a-3p was detected in patients with erosive OLP. ROC curve demonstrated the diagnostic value of miR-23a-3p for OLP with the AUC of 0.908, it can also distinguish erosive OLP from the non-erosive ones. MiR-23a-3p level was negatively associated with RAE (reticular, atrophic, erosive) score in OLP patients (r = − 0.790, P < 0.001). The in vitro experiments indicated that overexpression of miR-23a-3p reversed the promotive effect of LPS on HaCaT cell proliferation and reduced the protein levels of TNF-α and IL-6. The cyclin D1 (CCND1) was a direct target gene of miR-23a-3p, it was overexpressed in OLP cell models.Conclusion: MiR-23a-3p was at the low expression in OLP patients and showed close association with the disease severity. Overexpression of miR-23a-3p might inhibit keratinocyte proliferation and inflammatory response via targeting CCND1.Keywords: oral lichen planus, miR-23a-3p, keratinocyte cell, CCND1